PENERAPAN FLIPPED CLASSROOM DIINTEGRASIKAN DENGAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN NUMERASI SISWA SMA - Khoirin Nisya; Hepsi Nindiasari (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to determine the effect of applying the Flipped Classroom learning model integrated with Problem Based Learning on the numeracy skills of high school students. The research sample consisted of 39 experimental class students who used the flipped classroom model integrated with Problem Based Learning and 39 control class students who used the Problem Based Learning model from the population of SMAN 5 Serang city. The research method used was quasi experiment. The instrument used in collecting data was a test instrument in the form of a pretest and postest consisting of three description questions. The data were analyzed by one-way anova test with a significance level of 0.05 to see the average difference between the two classes. The results showed that the pretest value of numeracy skills obtained a Sig. 0.159 > 0.05 so that H_0 is accepted. meaning that the experimental class and control class have the same initial ability. then for the posttest value of numeracy skills obtained a Sig value. 0.21 <0.05 so that H_0 is rejected. This means that there is an average difference in numeracy skills between the experimental class and the control class. When viewed from the average numeracy skills of experimental class students are smaller than the control class, namely 40.05 < 51.51. Thus, the Problem Based Learning learning model is better than the Flipped Classroom model in improving the numeracy skills of high school students on the material of the system of linear equations of three variables